2014
DOI: 10.1007/s10120-014-0379-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of endoscopic submucosal dissection on additional gastric resections

Abstract: Background Widespread application of endoscopic submucosal dissection (ESD) for early gastric cancer (EGC) results in noncurative resection in some patients. The influence of preceding ESD on additional gastric resections has not been completely evaluated. Methods Endoscopic, surgical, and pathological records of 255 patients who underwent additional gastrectomy after noncurative ESD at a single prefectural cancer center from September 2002 to December 2010 were reviewed. The estimated gastric resection based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…A high prevalence of D2 lymphadenectomy was recorded because we used this treatment strategy for all cases with positive vertical margins even though the patients had early gastric cancer. We reported previously that it is rare for preceding ESD to necessitate alterations in gastric resection [19]. Forced conversion to total gastrectomy due to the effects of preceding ESD is a potential risk for patients, and this occurred in only one patient in the present study.…”
Section: Discussionmentioning
confidence: 50%
“…A high prevalence of D2 lymphadenectomy was recorded because we used this treatment strategy for all cases with positive vertical margins even though the patients had early gastric cancer. We reported previously that it is rare for preceding ESD to necessitate alterations in gastric resection [19]. Forced conversion to total gastrectomy due to the effects of preceding ESD is a potential risk for patients, and this occurred in only one patient in the present study.…”
Section: Discussionmentioning
confidence: 50%
“…Several studies [14][15][16] support similar results but also point that adhesion may result in difficult surgery and greater blood loss, and intended operative procedure can be changed due to contraction of the ESD scar near pylorus or cardia. [13][14][15]17 As all we know, laparoscopic gastrectomy has become standard treatment for early gastric cancer. Laparoscopic gastrectomy with adequate lymph node dissection can be safely applied for patients with non-curative ESD regarding postoperative complications and oncologic outcomes.…”
Section: Editorialmentioning
confidence: 76%
“…No relationship between the interval and perioperative outcome was recognized in this study. Kawata et al [18] reported no influence of additional gastric resection after ESD. However, they performed open gastrectomy for 93% cases (236/261 cases).…”
Section: Discussionmentioning
confidence: 98%